Medical education theory and practice - Dorman, Tim; Mann, Karen; Scherpbier, Albert; Spencer, John (Churchill Livingstone/Elsevier, 2011)
Medical Education: Theory and Practice is a new text linking the theory and the practice for graduate students and educators who want to go beyond the basics. The scholarship of medical education is, above all, a 'practice', but one that has a strong theoretical foundation. Neither theory nor practice stand still, and both are grounded in research. The novelty of this book lies in its interweaving of practice, theory, innovation and research